Dinamika Jender terhadap Akses Pelayanan Kesehatan Maternal Sembilan Etnis di Indonesia - Isfandari Siti; Selma Siahaan; Grace Wanggae; Ratna Widyasari; Aan Kurniawan; Ni Ketut Aryastami; Niniek Lely Pratiwi (Pusat Penelitian dan Pengembangan Humaniora dan Manajemen Kesehatan, 2019)
This is a review of maternal mortality risk due to preference of non skilled health worker delivery assistance among 9 ethnics applying gender analysis. Data obtained from 9 ethnograpic studies reports conducted by Pusat Humaniora. Estimation of maternal mortality rate (MMR) in Indonesia is between 305 (Supas) – 359 (Susenas) per 100.000 live birth. There is no single cause of maternal death. The greatest contributors 75% are due to direct cause namely bleeding, infection, hypertension, delivery complication and unsafe abortion. Government intervention prioritizes to prevent direct cause of maternal death through health service delivery improvement. Among them are midwives in village, PONEK, PONED. However MMR is still high. Social factors as Indirect causes such as poverty, distance, information, inadequate service and culture have not yet considered as important. In fact contribution of social factors cannot be neglected. This review explores gender dynamics of preferences on non skilled health worker delivery assistance from 9 ethnic in Sumatra, Jawa and NTT. The results showed each ethinc had different gender dynamics. Among which are gender relation in each culture. Some ethnic shows gender equity, while others believe woman have full responsibility of her pregnancy and delivery without assistance from others. Powerlessness of woman is indicated by preference of traditional birth attendant for delivery due to culture and comfort. Even the pregnant women herself did not aware that delivery is a life risk. However the studies showed there is no sharp inequity with strong preference to boy over girl. Accessibility, education, comfort perceived culture, and economy are important for delivery assisted by health providers.